Research on pressure fluctuation distribution law and rotor-stator interaction of pump-turbine in vaneless region of turbine mode - Yi, Chuanbao; Zhang, Zequan; Dong, Haiyang; Lu, Yonggang; Xu, Shuangquan; Li, Xiji; Sun, Chuanzhen; Zhang, Shuaishuai; Wang, Zhengwei (Frontiers in Energy Research, 2025)
The vibration issue of pumped storage power station unit will directly affect the safe and stable operation of the unit, and the pressure pulsation in the vaneless region is an important index to evaluate the stability of the unit. In order to study the pressure fluctuation characteristics of the vaneless region of the pumpturbine in the turbine mode, the unsteady numerical simulation of the maximum head condition and the rated head condition is carried out in this research. The amplitude-frequency characteristics of the pressure fluctuation in the vaneless region under different head and the influence of the internal flow characteristics on the pressure fluctuation are analyzed. The results show that the non-uniform pressure field is formed in the vaneless region due to the rotor-stator interaction (RSI) between the long and short blades of the runner and the guide vanes. The main frequency of pressure pulsation in the vaneless region is 5fn, which is half of the blade passing frequency (BPF), that is, the blade combination passing frequency.The main sub-frequencies are 10fn, 15fn and 20fn. In addition, the amplitude of pressure pulsation at each frequency under the rated head condition is higher than that under the maximum head condition. In a rotating cycle, the discrete blade vortex in the runner flow channel gradually accumulates and evolves into the big scale vortex on the side of the pressure surface of the short blade, which aggravates the pressure fluctuation in the vaneless region. The intensity of the vortex under the rated head condition is larger, which reasonably explains the reason why the pressure fluctuation amplitude under the rated head condition is larger.